Data-Driven Evaluation of ESP Textbook: Assessing Impact on Learning Outcomes for EFL Learners - Muhammad Najmi Al Habsyi; Maulida Zahrotun Niesrina; Abdul Syahid (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Abstract: This study evaluates the book “English for Specific Purposes”, a compilation of seven scholarly articles, aiming to assess the relevance and application of the theories and methods presented in the book to current ESP practices. Using a qualitative content analysis approach, the study examines the book’s strengths and weaknesses in supporting the development of ESP pedagogy. The analysis reveals that the book demonstrates a strong focus on alignment with learning objectives and offers a variety of teaching methods. However, greater attention is needed for technology integration and the development of specific language skills such as listening, reading, writing, and vocabulary. These findings provide valuable insights for material designers and educators to enhance the quality and accessibility of English for Specific Purposes textbooks in the future.